WAYS TO IMPROVE THE ENERGY EFFICIENCY OF ELECTRIC BUSES USING MODERN PHOTOVOLTAIC TECHNOLOGIES - Kulbashna, N.; Lukashova, N.; Daleka, V.; Skurikhin, V. (Municipal economy of cities. Series: «Economy science», 2025)
This work analyzes the latest research on the applications of photovoltaic panels on electric buses in different countries worldwide. It considers the implementation experience of such systems in Korea, India, the USA, Great Britain, and others. The research analyzed demonstrates that photovoltaic systems can supply the main part of the energy consumption of electric buses. This reduces the dependency on the energy grid, reduces the load on it, and increases the lifespan of batteries. This work also points out key technical and economic factors that will impact the choice of photovoltaic modules, particularly, their price, ongoing maintenance costs, and lifespan. The goal of this article is to research the energy-saving capabilities of photovoltaic technologies for electric buses. This work proposes a classification that demonstrates how to achieve more energy from photovoltaic panels when they are used on electric buses. The classification includes traditional approaches that are commonly used in the photovoltaic industry, in particular, the application of different chemical compounds and absorbing materials, changing modules’ architectures as well as mechanical and electric influences. The classification considers methods of obtaining maximum power by controlling photovoltaic systems with controllers and other electromechanical devices. It also considers the known methods of extending a useful panel’s surface area such as sliding from different sides and on a trailer. The proposed classification can be useful to transport businesses wanting to implement innovative solutions in the industry of electric city transportation. The article also evaluates the dependence of resource conservation indicators on the efficiency coefficient and utilization of a useful roof surface area for electric buses manufactured domestically. The application of photovoltaic panels in electric buses is a promising direction of development that will contribute towards reducing emissions, more efficient usage of energy resources, and improving ecological safety of city transportation.